Enhancing health outcomes for Māori elders through an intergenerational cultural exchange and physical activity programme: a cross-sectional baseline study - John G. Oetzel; Yingsha Zhang; Yingsha Zhang; Sophie Nock; Pare Meha; Huia Huriwaka; Maramena Vercoe; Tania Tahu; Joanne Urlich; Rachel Warbrick; George Brown; Shirley Keown; et al. (Frontiers Media S.A., 2023)
BackgroundThe study offers baseline data for a strengths-based approach emphasizing intergenerational cultural knowledge exchange and physical activity developed through a partnership with kaumātua (Māori elders) and kaumātua service providers. The study aims to identify the baseline characteristics, along with correlates of five key outcomes.MethodsThe study design is a cross-sectional survey. A total of 75 kaumātua from six providers completed two physical functioning tests and a survey that included dependent variables based in a holistic model of health: health-related quality of life (HRQOL), self-rated health, spirituality, life satisfaction, and loneliness.ResultsThe findings indicate that there was good reliability and moderate scores on most variables. Specific correlates included the following: (a) HRQOL: emotional support (β = 0.31), and frequent interaction with a co-participant (β = 0.25); (b) self-rated health: frequency of moderate exercise (β = 0.32) and sense of purpose (β = 0.27); (c) spirituality: sense of purpose (β = 0.46), not needing additional help with daily tasks (β = 0.28), and level of confidence with cultural practices (β = 0.20); (d) life satisfaction: sense of purpose (β = 0.57), frequency of interaction with a co-participant (β = −0.30), emotional support (β = 0.25), and quality of relationship with a co-participant (β = 0.16); and (e) lower loneliness: emotional support (β = 0.27), enjoyment interacting with a co-participant (β = 0.25), sense of purpose (β = 0.24), not needing additional help with daily tasks (β = 0.28), and frequency of moderate exercise (β = 0.18).ConclusionThis study provides the baseline scores and correlates of important social and health outcomes for the He Huarahi Tautoko (Avenue of Support) programme, a strengths-based approach for enhancing cultural connection and physical activity.